Systemic Treatment of Vitreous Inflammation - John B. Christoforidis; Susie Chang; Angela Jiang; Jillian Wang; Colleen M. Cebulla (Mediators of Inflammation)
Non infectious vitreous inflammation is often vision threatening and can be associated with potentially life-threatening systemic conditions. Treatment is often challenging as it involves systemic medications that can be associated with adverse effects. The classes of drugs are ever expanding and include corticosteroids, antimetabolites, alkylating agents, T-cell and calcineurin agents, biologic agents, and interferons. Each class of systemic therapy for non-infectious vitreous inflammation is reviewed. We discuss the mechanisms of action, usual clinical dosages, the specific conditions that are treated, the adverse effects, and usual course of treatment for each class of therapy.